2000
DOI: 10.1007/s001340051291
|View full text |Cite
|
Sign up to set email alerts
|

Propofol improves recovery from paraquat acute toxicity in vitro and in vivo

Abstract: Post i.v. injection of propofol is protective against paraquat-induced damage. Propofol can be given during mechanical ventilatory support after paraquat poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Yeh et al [61] documented that N ‐acetylcysteine, a precursor of glutathione and a free radical scavenger reduced paraquat‐induced toxicity and mortality in rats. Other antioxidants including propofol and trolox also were reported to improve the recovery from acute paraquat toxicity in mice [62].…”
Section: Discussionmentioning
confidence: 99%
“…Yeh et al [61] documented that N ‐acetylcysteine, a precursor of glutathione and a free radical scavenger reduced paraquat‐induced toxicity and mortality in rats. Other antioxidants including propofol and trolox also were reported to improve the recovery from acute paraquat toxicity in mice [62].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of benzoquinone (BQ; 0.2 mM, Sigma-Aldrich) were evaluated after 10 min of incubation in BQadded medium. Intracellular H 2 O 2 production in HeLa cells by PQ was detected using 2Ј,7Ј-dichlorofluorescein-diacetate (DCFH; Molecular Probes) (17,18). Briefly, cells were pretreated with 1 mM PQ for 1 h at 37°C, and then the cells were incubated with 5 M DCFH for 20 min in the dark.…”
Section: Intracellular Ros Productionmentioning
confidence: 99%
“…It is important to be able to provide safe anesthesia with neuroprotective potential in such cases. Propofol post-conditioning has shown protection against hypoxic injury and paraquat toxicity in in vitro and in vivo conditions [1,2]. Previous studies have indicated that some anesthetics have neuroprotective effects, given their ability to suppress cerebral metabolic rate, antagonize glutamate-mediated excitotoxicity, and enhance inhibitory synaptic transmission [36].…”
Section: Introductionmentioning
confidence: 99%